Human papillomavirus infection and intrauterine growth restriction: a data-linkage study. (17th January 2019) - Ford, Judith Helen; Li, Ming; Scheil, Wendy; Roder, David
Abstract: Objective: Using unbiased population data, to examine whether having a positive Pap smear, and thus a high probability of Human Papilloma Virus (HPV) infection, is a significant risk factor for intrauterine growth restriction (IUGR) in a subsequent pregnancy. Study design and methods: Two independent population-based databases, namely the South Australian Perinatal Statistics Collection and the South Australian Cervical Screening Database, were deidentified and linked by the SANT Datalinkage Service. Analyses were performed on cases where Pap smear screening data was available for up to 2 years prior to a singleton live birth. Population characteristics and pregnancy related data were compared statistically by normal birth weight versus IUGR (10th percentile – known as small for gestational age (SGA), small for gestational age) and (3rd percentile birth weight – known as VLBW, very low birth weight). The association between cervical screening results and IUGR was assessed using generalized linear log binomial regression models. Results: A total of 31, 827 women met the criteria. Of these, 1311 women (4.1%) had a positive Pap smear within 2 years of the current pregnancy. Those having a positive Pap smear were more likely to have a baby with IUGR than those with negative smear results. For SGA, 5.8% babies were from mothers with positive Pap smears compared to 4.0% with negative smears indicating a 40% higher risk of having an SGA baby (95%CI 20–70%) among women with positive Pap smears. For VLBW, 7.6% mothers had positive Pap smears compared with 4.0% with negative smears ( p < .001), which reflects a 90% increased risk (95%CI 40–150%). These associations reduced to 20% (95%CI 1–40%) and 50% (95%CI 10–100%) for SGA and VLBW, respectively, after adjusting for all other significant covariates including maternal age, ethnicity, marital status, occupation, smoking, pregnancy history, and maternal health during pregnancy. Conclusions: Mothers with a positive Pap smear have an increased risk of IUGR, especially for VLBW, which is independent of other risk factors. The results confirm previous findings in a small study and emphasise the need to consider the risks of both cancer and IUGR in all HPV vaccination programs.